PENGARUH PRODUCT QUALITY DAN SERVICE QUALITY TERHADAP REPURCHASE INTENTION DENGAN CUSTOMER SATISFACTION SEBAGAI INTERVENING : STUDI KASUS PADA PENGUNJUNG DI SALAH SATU TOKO RETAIL DI JAKARTA TIMUR - Siregar, Riyadi Hamzah; Rizan, Mohamad; Febrilia, Ika (Yayasan Education and Social Center, 2023)
This study aims 1) to determine the effect of product quality on customer satisfaction, 2) to determine the effect of Service Quality on customer satisfaction, 3) to determine the effect of customer satisfaction on repurchase intention, 4) to determine the effect of Product Quality on repurchase intention, 5) to determine the effect of Service Quality on repurchase intention, 6) to determine the effect of Product Quality of repurchase intention through customer satisfaction as intervening, 7) to determine the effect of Service Quality on repurchase intention through customer satisfaction as intervening, at the Miniso Store in Jakarta. The survey method with the instrument in the form of a questionnaire is a method of collecting data that researchers use. The sample of this study was 200 respondents who had bought Miniso products twice in the last six months at the Miniso store in Jakarta. Data were analyzed using SPSS version 22 and SEM (Structural Equation Model) from lisrel software version 8.80 to process and analyze research data. The test results of the results of the hypothesis test showed that all hypotheses were accepted.